ANALYSIS OF THE CLINICAL CHARACTERISTICS OF PERIANAL FISTULISING CROHN’S DISEASE IN A SINGLE CENTER - XU,Min-Min (2019)
ABSTRACT Background: Clinical characteristics are keys to improve identification and treatment of Crohn´s disease (CD) so that large sample analysis is of great value. Aim: To explore the clinical characteristics of perianal fistulising CD. Methods: Analysis of 139 cases focused on their clinical data. Results: The proportion of males and females is 3.3:1; the mean age is 28.2 years; 47.5% of patients had anal fistula before CD diagnosis. Patients with prior perianal surgery and medication accounted for 64.7% and 74.1% respectively. The L3 type of lesion was present in 49.6% and the B1 and B2 types for 51.8% and 48.2% respectively; complex anal fistula was diagnosed in 90.6%. Symptoms of diarrhea were found in 46% and perianal lesions alone in 29.5% of patients. Abnormal BMI values was present in 44.6%; active CD activity index in 64.7%; and 94.2% had active perianal disease activity index. A proportion of patients manifest abnormal C-reactive protein, erythrocyte sedimentation rate, platelet, hemoglobin and albumin. Conclusion: We suggest that patients with anal fistula associated to these clinical features should alert the medical team to the possibility of CD, which should be further investigated through endoscopy and imaging examination of alimentary tract to avoid the damage of anal function by routine anal fistula surgery.